SEISMIC HAZARD POTENTIAL ANALYSIS IN YOGYAKARTA BASED ON HVSR CURVE ESTIMATION - Natanael Zega, Brilian
In 2006, the Special Region of Yogyakarta was shaken by a destructive earthquake. The United States Geological Survey (USGS) recorded that the earthquake had a magnitude of 6,3 Mw at a depth of 12,5 km below the surface that was triggered by strike slip fault activity. The present study aims to estimate seismic hazard potential in the Yogyakarta region. We used data recorded from 15 seismic stations from the GFZ network in 2006 spread across Yogyakarta Province. Then the data is analyzed to determine the H/V curve by using Geopsy software. Horizontal to Vertical Spectral Ratio (HVSR) is one method that can be used to estimate the dominant frequency value and amplification factor value in the subsurface layer. The distribution of domminant frequency values is obtained in the range of 0,567-13,7 Hz and the distribution of amplification factor values in the range of 1,17-7. The inversion process is implemented on the H/V curve by using Dinver software to obtain the value of Vs in the subsurface. The distribution of Vs values ranges between 157-1464 m/s and the distribution of Vs30 between 240-600 m/s with a misfit of 0,38-0,65. Based on the soil classification to Vs30, the Yogyakarta area is dominated by SD and SC soil types. Subsequently, the dominant frequency, amplification factor, and Vs30 were mapped to understanding the subsurface structure beneath the Yogyakarta region. The results of the mapping analysis indicate that Bantul is an area with the highest potential of seismic hazard.